An Introduction to the Combustion of Carbon Materials. Issue 54 (25th July 2022) - Picheau, Emmanuel; Amar, Sara; Derré, Alain; Pénicaud, Alain; Hof, Ferdinand
Abstract: Combustion is arguably as old as homo sapiens ability to observe and use fire. Despite the long tradition of using carbon combustion for energy production, this reaction is still not fully understood. This can be related to several facts that are intertwined and complicate the investigation, such as the large variety of possible carbon structures, the actual surface structure, porosity, the solid‐gas nature of this reaction, diffusion limitation and fundamental reaction steps. In this review, a brief history of carbon combustion science is given, followed by a detailed discussion of the most important aspects of carbon combustion. Special attention is given to limitations for example diffusion. In carbon combustion, kinetic control can rarely be observed. The literature of the fundamental reaction steps actually occurring on the carbon framework is reviewed and it becomes apparent that the reaction is occurring primarily on defects on the basal plane. Thus, the reaction between oxygen and carbon may be used as an analytical tool to provide further insights into novel materials, for example synthetic carbon materials, fibres and graphene type materials. Mastering the combustion reaction in all its complexity may prove to be very valuable in the future. Abstract : Looking back over centuries of research on carbon combustion, this reaction has literally fuelled the development of mankind and truly astonishing technological advancement. Carbon combustion is complex and interplay of different limitations such as diffusion, heat/mass transfer, and reactivity of active sites is observed. The understanding and a unifying concept of carbon combustion may prove to be valuable also for the understanding of novel carbon nanomaterials, such as fibres or graphene like materials.